두 가지 장비를 이용한 각막 지형도 검사의 비교 - 이동민; Dong Min Lee; 안지민; Ji Min Ahn; 서경률; Kyoung Yul Seo; 김응권; Eung Kweon Kim; 김태임; Tae Im Kim (Daihan angwa haghoi jabji, 2012)
목적: 각막지형도 측정 장비인 Pentacam과 Sirius로 평가한 전안부 측정값을 비교하고자 하였다. 대상과 방법: 정상각막 및 굴절수술을 받은 환자를 대상으로 전안부 측정값을 비교하였다. 결과: 총 44명 88안을 대상으로 Pentacam과 Sirius를 이용하여 전안부 검사를 시행한 결과 정상각막군에서 두 기계의 측정치가 각막 중심두께(p=0.693), 가장 얇은 부분의 각막두께(p=0.386), 전방용적(p=0.155), 동공크기(p=0.650)에서 유의한 차이를 보이지 않았고, 각막용적(p=0.023), 전방각(p>0.001) 각막굴절률(p<0.001)에서는 유의한 차이를 보였다. 굴절교정수술군에서는 각막중심두께 (p=0.056)를 제외한 가장 얇은 각막두께(p=0.019), 전방깊이(p<0.001), 전방용적(p<0.001), 전방각(p<0.001), 각막용적(p<0.001), 동공크기(p<0.001), 각막굴절률(p<0.001)에서 두 검사 간에 유의한 차이를 보였다. 결론: Pentacam과 Sirius에서 측정값들은 정상각막에 비해 굴절수술 직후에 더 많은 계측치에서 유의한 차이를 보이므로 임상적용에 이를 고려하여야 할 것이다. Purpose: To compare the corneal measurements of Sirius and Pentacam in normal cornea and post-corneal refractive surgery patients. Methods: Subjects were tested by Pentacam (OCULUS, Wetzlar, Germany), and Sirius (CSO, Firenze, Italy). Measurements included central corneal thickness, thinnest corneal thickness, anterior chamber depth, anterior chamber volume, iridocorneal angle, corneal volume, pupil size, and curvature of cornea. Results: A total of 88 eyes from 44 patients were included in the present study. When comparing Sirius and Pentacam in the normal cornea, corneal thickness (p = 0.693), thinnest corneal thickness (p = 0.386), anterior chamber depth (p = 0.155), anterior chamber volume (p = 0.650), and pupil diameter (p = 0.124) did not differ significantly. Corneal curvature (p < 0.001), corneal volume (p = 0.023), and iridocorneal angle (p < 0.001) were statistically different. When comparing Sirius and Pentacam in post-corneal refractive surgery patients, corneal thickness (p = 0.056) did not differ significantly. There was a statistical difference in corneal curvature (p < 0.001), thinnest corneal thickness (p = 0.019), anterior chamber depth (p < 0.001), anterior chamber volume (p < 0.001), iridocorneal angle (p < 0.001), corneal volume (p < 0.001), and pupil diameter (p < 0.001). Conclusions: Anterior segment measurements with Pentacam and Sirius showed differences in post-corneal refractive surgery patients.